The contentious process of declaration of detrimental to public interest: Fourteen years after its incorporation in Peruvian law - Morón Urbina, Juan Carlos (2015)
This article explains the contentious process of harmfulness. Thus, the author mentions that the foundation of the process of harmfulness has been on our right the survival of the Administrative security of the legality and the public interest butlimiting the self-enforcement, the requirement of belief in authority to pursue the annulment of an administrative act and to ensure the due process of law is being administered.